Determinantes da transparência municipal: análise empírica - Freitas, Ivone (2016)
Transparency is universally regarded as an element of good governance. The new form of activity of local governments, including the accountability of these voters/taxpayers, medium, control bodies and other interested parties to monitor the activities of governments emphasize the attention given to transparency and its determinants. The economic, social and financial context that local governments are subject requires them to be as transparent as possible in order to create greater involvement of citizens in the affairs of political and simultaneously promote greater accountability of the local voters to those same citizens. However, transparency levels are often below the standards required for public or government agencies. Particularly, at the local level, the transparency practices may vary substantially from one local government to another. Despite recent efforts, the current empirical research does not provide definitive answers yet about the reasons for the fluctuations in the levels of transparency. The main objective of this study was to identify the determinants of transparency in Portuguese municipalities. Using the Municipal Transparency Index of years 2013 and 2014 we tried to study the socio-demographic variables, political and economic-financial to the universe of 308 Portuguese municipalities, through the test the research hypotheses previously formulated in the light of agency theory. Statistical results indicate that the size, individuals with age between 15 and 74 years old use the internet, education level, aging index, unemployment rate, financial autonomy and net debt are determinants of transparency in Portuguese municipalities. There was no empirical evidence for the political variables, e.g., form of government, political ideology and political/electoral participation.